Protein feed stimulates the development of mandibular glands of honey bees (Apis mellifera) - Camilli, Marcelo P [UNESP]; de Barros, Daniel C B [UNESP]; Justulin, Luis A [UNESP]; Tse, Marcos L P [UNESP]; Orsi, Ricardo de Oliveira [UNESP] (Taylor & Francis, 2020)
This study assessed the effects of different protein levels on the development of the mandibular gland (MG) in six-day-old worker bees (Apis mellifera) during the dearth period. Twenty colonies were randomly assigned to one of four experimental diets containing 0%, 23%, 25%, or 27% crude protein (CP), with five replicates each. The experimental diets were composed of feed meal and honey sirup. Each colony was provided with 30 g of formulated feed every 3 days over a 36-day period. At the end of the experimental period, ten six-day-old worker bees were collected from each treatment for the morphological analysis of their MGs. The area of the MG was significantly larger in the bees fed protein-enriched feeds than in the controls. The height of the secretory cells in the MG was also significantly greater in all colonies fed protein-enriched feed than in the control group. However, the group that received the feed with 23% CP had significantly taller secretory cells than the other groups. Based on regression analysis, the ideal level of protein in the diet for the development of the MG was 22.2% CP. Thus, the use of protein-enriched feed promotes greater increases in the area and height of secretory MG cells in six-day-old honey bee workers.
Keywords: beekeeping; morphology; nutrition; protein; royal jelly; supplementation